2020
DOI: 10.1371/journal.pone.0241362
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of QT prolongation by buprenorphine cannot be explained by direct hERG channel block

Abstract: Buprenorphine is a μ-opioid receptor (MOR) partial agonist used to manage pain and addiction. QTC prolongation that crosses the 10 msec threshold of regulatory concern was observed at a supratherapeutic dose in two thorough QT studies for the transdermal buprenorphine product BUTRANS®. Because QTC prolongation can be associated with Torsades de Pointes (TdP), a rare but potentially fatal ventricular arrhythmia, these results have led to further investigation of the electrophysiological effects of buprenorphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Characterizing the exposure‐response relationship is important to determine the potential amount of QTc prolongation in certain patient subgroups that may be subjected to higher drug exposures and evaluate whether the QTc prolongation plateaus, suggesting an indirect mechanism that may be of lower risk. There are multiple potential indirect mechanisms that can lead to QTc prolongation (i.e., not acting through direct ion channel effects), such as from autonomic nervous system effects, 33,34 changes in body temperature, 35 electrolyte abnormalities, 36 and others still being defined ( Figure 6 ) 37 . Further investigation should differentiate which mechanisms can be associated with TdP vs. those that are not.…”
Section: Ich E14/s7b Working Group Proposed Stage 2 Of Qandas – Providimentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing the exposure‐response relationship is important to determine the potential amount of QTc prolongation in certain patient subgroups that may be subjected to higher drug exposures and evaluate whether the QTc prolongation plateaus, suggesting an indirect mechanism that may be of lower risk. There are multiple potential indirect mechanisms that can lead to QTc prolongation (i.e., not acting through direct ion channel effects), such as from autonomic nervous system effects, 33,34 changes in body temperature, 35 electrolyte abnormalities, 36 and others still being defined ( Figure 6 ) 37 . Further investigation should differentiate which mechanisms can be associated with TdP vs. those that are not.…”
Section: Ich E14/s7b Working Group Proposed Stage 2 Of Qandas – Providimentioning
confidence: 99%
“…There are multiple potential indirect mechanisms that can lead to QTc prolongation (i.e., not acting through direct ion channel effects), such as from autonomic nervous system effects, 33,34 changes in body temperature, 35 electrolyte abnormalities, 36 and others still being defined (Figure 6c). 37 Further investigation should differentiate which mechanisms can be associated with TdP vs. those that are not. Furthermore, an integrated risk assessment could consider a combination of clinical/ pharmacodynamic factors with nonclinical assays to rule in or out certain mechanisms if needed.…”
Section: Ich E14/s7b Working Group Proposed Stage 2 Of Qandas -Providinmentioning
confidence: 99%
“… 34 Despite these findings, those authors and others have not found any association between transdermal buprenorphine and pro-arrhythmic effects. 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…34 Despite these findings, those authors and others have not found any association between transdermal buprenorphine and pro-arrhythmic effects. 34,35 Long-term use of buprenorphine will result in dependency on the drug; that is the normal and expected result of chronic use of any opioid. A once-only use of a sevenday patch treatment of buprenorphine should not result in dependence or tolerance.…”
Section: Safetymentioning
confidence: 99%
“…It has been suggested that buprenorphine is the safer option for treating opioid use disorder in heroin users and those with, or that have experienced, methadone-induced torsade de pointes [ 32 ]. However, due to unknown mechanisms, high-dose transdermal buprenorphine can significantly increase QTc interval [ 34 ]. Additionally, buprenorphine can substantially prolong the QTc interval when combined with antiretroviral agents [ 35 ].…”
Section: Interactions Between Antipsychotics and Non-psychotropic Med...mentioning
confidence: 99%